The effect of aging on context use and reliance on context in speech: A behavioral experiment with Repeat–Recall Test - Sun, Jiayu; Zhang, Zhikai; Sun, Baoxuan; Liu, Haotian; Wei, Chaogang; Liu, Yuhe (Frontiers in Aging Neuroscience, 2022)
Purpose: To elucidate how aging would affect the extent of semantic context use and the reliance of semantic context measured with the Repeat-Recall Test (RRT). Methods: A younger adult group (YA) between 18 and 25 years of age and an older adult group (OA) between 50 and 65 years of age were recruited. Both groups were tested on the RRT: sentence repeat and delayed recall tasks as well as assessing subjective listening effort and noise tolerable time, under two noise types and seven signal-to-noise ratios (SNR). Performance-Intensity curves were fitted. The performance in SRT50 and SRT75 were predicted. Results: Generally, on the repeat task, OA used more semantic context and were more reliant on semantic context compared to YA. On the recall task, OA used less semantic context but relied more on context compared to YA. Age did not affect subjective listening effort but significantly affected noise tolerable time. Both age groups could use more context in SRT75 than SRT50 on four tasks of RRT. When focusing on the same SRT between the two age groups, however, YA could use more context in repeat and recall tasks than OA. Conclusions: Age would make a difference in semantic context use and reliance on semantic context. Even though OA used more context in speech recognition, they may still fail in speech information maintenance (recall) even with the help of semantic context. OA also tend to rely more on context during these two tasks. The amount of context use also influenced by SRT.